EVALUATION OF THE PROVISION OF SPECIFIC BICYCLE LANES IN THE MALANG CITY - Nika Devi Permata Wijaya; Zaid Dzulkarnain Zubizaretta; Marisa Wahyu Kurniasari; Karina Pangamiani (Universitas Islam Malang, 2023)
Even though special bicycle lanes have been provided, there are still many obstacles that make the provision of these lanes ineffective. Problem parking vehicles in bicycle lanes, as well as the lack of awareness of motorists who use special bicycle lanes, can threaten the safety of their users. Based on the results of the analysis using the IPA (Importance Performance Analysis) method, it is known that the highest service suitability level includes attractive bicycle path designs, harmonious land use and vegetation, and green or white colors on the bicycle lane symbol. The IPA method is divided into four quadrants where quadrant one has low satisfaction while the level of importance is high. There are signs for cyclists, command and prohibition signs, street lighting, backrests that allow bicycles to be locked, cyclists are prioritized over motorists, and height and pavement materials are safe for cyclists, therefore improvements need to be made to create special lanes a bicycle that can bring a sense of security and comfort to the user. Keywords: Bike Lane; Importance Performance Analysis Method; Evaluation